Observations on features of a research interview - Andrew P. Carlin (Ciências Sociais Unisinos)
This paper looks at some constitutive features of interviews and the presentation of findings from interviews. A set of open-ended interviews was conducted after the bombing of Manchester city-centre, with residents, people who worked in the city centre, and members of the emergency services who had attended the scene. Regardless of the substantive topic of inquiry, a naturalistic approach to the structures of talk within these interviews makes available collaborative linguistic phenomena produced by interviewer and interviewees. These routine practices included designing talk for a specific interlocutor, the use of referents or indexical expressions, the deployment of membership categories and the telling of stories. As a single case analysis, a sequence of talk from one interview is used to highlight the specificity of these ordinary features.